Merjenje določenih vidikov skladenjske kompleksnosti v pisnih besedilih slovenskih osnovnošolcev - Gaberšček, Neža (Jezik in slovstvo, 2018)
Complexity is a common term in linguistics, yet its treatment is marked by inconsistency. In applied linguistics, it is defined as one of the dimensions of language proficiency and performance. Complexity is rarely measured in written texts of native speakers and is mostly treated as a measure of language development. In the present article, new criteria for language complexity that include various aspects of the term are established and the known methods are applied to measure the syntactic complexity in written texts of Slovenian schoolchildren.
Keywords: osnovnošolci; pisna besedila; pragmatika; skladenjska kompleksnost; skladenjske strukture; slovenščina; strukturna kompleksnost